Effectiveness of EMC2 Social Emotional Attitudes on Mental Health of Elementary School Students - Wulandari, Ayu; Rahayu, Sella; Azainil, Azainil (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This study addresses the problem of declining character values and increasing mental health challenges among elementary school students, which are exacerbated by rapid social changes and insufficient emotional support in educational settings. The research aims to evaluate the effectiveness of the EMC² Social Emotional Attitude program in supporting students' mental health and developing their emotional and social skills. Quantitative research design, data were collected using questionnaires and in-depth interviews with selected participants. The findings reveal that the majority of students reported significant benefits from the EMC² program, including improvements in emotional regulation, self-esteem, and classroom interaction. Students felt more valued, confident, and emotionally stable in their daily school experiences. These results confirm that the EMC² approach has a positive impact on students' mental health and provides a viable model for character education in elementary schools. The study highlights the importance of ongoing collaboration among teachers, schools, and families in fostering the development of students' social-emotional competencies and overall well-being.